Effect of anode interfacial modification on the performance of laminated flexible ITO‐free organic solar cells. Issue 4 (27th January 2021) - Lin, Zesen; Guan, Wei; Cai, Wanzhu; Wang, Le; Wang, Xiaojing; He, Zhicai; Hou, Lintao
Abstract: Lamination technique is one of the most promising and effective approaches to produce flexible organic solar cells (OSCs), with the combination of high throughput and simultaneous encapsulation. In this study, flexible ITO‐free OSCs were successfully fabricated by lamination technique under the optimized temperature and pressure. It is found that the introduction of hole interface layer of PEDOT:MoO3 helps to improve both the film hydrophobicity and the carrier extraction. A high efficiency improvement of about 30% is obtained in the interface‐modified laminating flexible ITO‐free OSCs compared to the conventional laminated device. This work illustrates that anode interface engineering has a significant effect on the improvement of performance of roll‐to‐roll laminated and self‐encapsulated OSCs. Abstract : Flexible ITO‐free organic solar cells were successfully fabricated and optimized with lamination technology. The PEDOT:MoO3 hole interfacial layer was introduced into the structure, increasing in the short circuit current and the power conversion efficiency of about 30%. PEDOT:MoO3 is found out to promote both the film hydrophobicity and the carrier extraction.